2008
DOI: 10.1111/j.1467-9221.2007.00611.x
|View full text |Cite
|
Sign up to set email alerts
|

Moral Conviction and Political Engagement

Abstract: The 2004 presidential election led to considerable discussion about whether moral values motivated people to vote, and if so, whether it led to a conservative electoral advantage. The results of two studies-one conducted in the context of the 2000 presidential election, the other in the context of the 2004 presidential election-indicated that stronger moral convictions associated with candidates themselves and attitudes on issues of the day uniquely predicted self-reported voting behavior and intentions to vot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
182
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 212 publications
(193 citation statements)
references
References 25 publications
8
182
1
2
Order By: Relevance
“…Graham et al (2009) said that liberals mostly endure the harm/care and fairness/reciprocity foundations of morality while conservatives use five foundations of morality which are harm/care, fairness/reciprocity, in-group/loyalty, authority/respect, and purity/sanctity. Skitka and Bauman (2008), on the other hand, demonstrated that the conservatives and liberals are not different in their political engagement, they stated that "the effects of moral conviction on political engagement are equally strong for those on the political right and left" (p. 50).…”
Section: Introductionmentioning
confidence: 99%
“…Graham et al (2009) said that liberals mostly endure the harm/care and fairness/reciprocity foundations of morality while conservatives use five foundations of morality which are harm/care, fairness/reciprocity, in-group/loyalty, authority/respect, and purity/sanctity. Skitka and Bauman (2008), on the other hand, demonstrated that the conservatives and liberals are not different in their political engagement, they stated that "the effects of moral conviction on political engagement are equally strong for those on the political right and left" (p. 50).…”
Section: Introductionmentioning
confidence: 99%
“…Et l'on ne peut que reconnaître les limites inhérentes aux enquêtes quantitatives et statistiques pour apprécier toute la complication des enjeux relationnels et identitaires sousjacents ainsi que les effets de leur subjectivation individuelle. Néanmoins, les résultats de cette étude confirment des observations menées dans le cadre d'enquêtes qualitatives (Muxel, 2008 ;Duret, 2010), mais aussi d'investigations d'ordre statistique (Zuckerman, 2005 ;Zuckerman et al, 2007 ;Stitka et Bauman, 2008). Par ailleurs, ils corroborent certaines évolutions significatives des reconfigurations de l'ordre familial, et plus largement de l'ordre privé, dans les sociétés de la postmodernité.…”
Section: Revue Française De Sociologie 56-4 2015unclassified
“…Moreover, there is evidence that moral framings of public policy issues affect engagement according to political orientation. That is to say, different forms of moral framing resonate to a greater or less extent with differing political rationalities (Skitka and Bauman 2008, Feinberg and Willer 2013, Vainio and Makiniemi 2016. If that hypothesis holds true, then it is important to examine how moral framings appear in public discourse and the different forms that they take in order to better understand issues of political legitimacy.…”
Section: Introductionmentioning
confidence: 99%